PENGEMBANGAN MODEL PEMBENTUKAN SIKAP MAHASISWA TERHADAP PROFESI GURU - Ali Muhson (Jurnal Kependidikan, 2008)
The study was aimed atfinding out (1) the category of the student s attitude of the teacher profession in FISE UNY; (2) the effect of the family sphere and the peer toward the student s perception of the teacher profession; and (3) the effect of thefamily sphere, thepeer, and the student s perception of the teacher profession toward the student s attitudes of the teacher profession. The population of the study consisted of the students of the Education Department/Study Program in FISE UNY to the total of 2.472 students. A total of 309 students was sampled as the  research subjects using the proportional cluster random sampling technique for selection. The data were collected by way of the questionnaire, and analyzed by the path analysis technique. The study found out that (1) most of the students in FISE  UNY had favourable attitudes towards the teacher profession; (2) the family sphere and the peer had a positive direct effect towards the perception of the teacher profession; and (3) thefamily sphere, the peer, and the perception of the teacherprofession had apositive direct effect towards attitudes of the teacherprofession